Penerapan Fuzzy Sugeno untuk Menentukan Jumlah Pembelian Keripik Singkong - Jesica Nababan; Alvianti Nurjanna; Melani Tri Rahayu (LPPM STIKOM Tunas Bangsa, 2020)
The existence of small industries shows their existence in improving the economy. Small industries have the ability to utilize raw materials and produce goods and services. Evidence of the existence of a small industry that is by opening a new employment so that it can reduce unemployment. Likewise with the small industry of cassava chips. Along with the increasingly globalized era of modernization in which small industries began to develop, both through increased technology and increased productivity so that the competition is increasingly tightened among small business owners. Likewise with the small industry of cassava chips experiencing intense competition so it is necessary to have business strategies in business development. One of the reasons why small industries fail to compete is the lack of marketing strategies. The purpose of this study was to determine the number of purchases of Harahap cassava chips with the Sugeno method of fuzzy inference based on inventory data and sales data. This study uses three variables, namely inventory, sales and purchases by having two inputs, namely inventory and sales and one output, namely purchasing. The results of the application of the Sugeno fuzzy method can help the company to determine the number of purchases of cassava chips with a success rate of 88.88%.